(untitled) (Research, Society and Development, 2020)
Several surveys carried out at the beginning of the 21st century have been showing intense indications of climate trends, on the global, regional and local scales. In this context, the objective is to analyze the thermal and annual thermal trends of maximum and minimum temperatures in Bom Jesus do Piauí, between the years (1960-2018), and to discuss their possible causes. Maximum and minimum air temperature (ºC) data acquired from the National Institute of Meteorology were used. For the data series, monthly averages and annual and seasonal totals corresponding to the summer, autumn, winter and spring seasons were calculated. The results made it possible to delimit the climatic behavior in the studied area, providing delimitations of a hot and / or cold period, serving as an alert to the authorities and decision makers, for a better agricultural and agribusiness planning. The fluctuations in temperatures are due to the synoptic systems operating at the time of the rainy and dry periods, as well as the impacts on the environment and the actions of the large-scale transient synoptic systems and their local and regional scale. These climatic trends were observed on a regional and local scale and were observed in the studied municipality. The temporal characterization, on a monthly and annual scale, generated simulated values very close to the observed values, a fact confirmed by statistical indices of satisfactory performance.